PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN - Asri Ayu Adisti; Ni Nyoman Sawitri, Dovina Navanti, Hapzi Ali, Muhammad Asif Khan (BORJUIS: JURNAL OF ECONOMY, 2024)
This article provides a detailed literature review regarding the influence of workload and compensation on employee performance. This article examines theoretical concepts, empirical findings and identifies the relationship between workload and compensation on employee performance and individual performance results using a literature synthesis. Based on the literature review, there is strong evidence that what can improve performance and compensation is the appropriateness of the workload given based on individual abilities. Excessive workload can cause fatigue and decreased performance. Apart from that, providing compensation in accordance with the performance given by employees also has a big influence on employee performance